'It's law Jim, but not as we know it': the public law techniques of ungovernance. (2nd July 2020) - Bell, Christine
ABSTRACT: Ungovernance involves circumnavigating disagreement over the nature and purposes of government itself. Ungovernance, despite its name, does not imply a lack of governance and therefore a lack of law, but requires legal techniques to be enabled. While government requires clear stable rules for making laws that ensure that those laws are in turn open, clear, stable and prospective in application, ungovernance is enabled by legal techniques such as: re-iterated constitution-making; institutionalised strategic dissonance; regime assemblage; legalised reset; and legal postponement or deferment (here termed 'tajility'). This 'new public law' retains the same symbiotic relationship to ungovernance that more traditional public law has to governance. Just as the old public law was bound up with the emergence of the modern concept of statehood, the new public law is bound up with a post-post-modern – or performative – 'fragment statehood'.